2017
DOI: 10.1371/journal.pone.0171041
|View full text |Cite
|
Sign up to set email alerts
|

Early BCR-ABL1 Transcript Decline after 1 Month of Tyrosine Kinase Inhibitor Therapy as an Indicator for Treatment Response in Chronic Myeloid Leukemia

Abstract: In chronic myeloid leukemia (CML), early treatment prediction is important to identify patients with inferior overall outcomes. We examined the feasibility of using reductions in BCR-ABL1 transcript levels after 1 month of tyrosine kinase inhibitor (TKI) treatment to predict therapy response. Fifty-two first-line TKI-treated CML patients were included (imatinib n = 26, dasatinib n = 21, nilotinib n = 5), and BCR-ABL1 transcript levels were measured at diagnosis (dg) and 1, 3, 6, 12, 18, 24, and 36 months. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Since prognostic information available even as early as 3 months may be too late for effective intervention in patients who experience early transformation 24 , we evaluated this optimal time point as being 22 days after the start of treatment in our cohort. Patients with a more rapid decline (BCR-ABL1 halving time ≤22 days) had a higher chance of ultimately achieving MMR and therefore a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since prognostic information available even as early as 3 months may be too late for effective intervention in patients who experience early transformation 24 , we evaluated this optimal time point as being 22 days after the start of treatment in our cohort. Patients with a more rapid decline (BCR-ABL1 halving time ≤22 days) had a higher chance of ultimately achieving MMR and therefore a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the fact that the actual baseline level of BCR-ABL1 transcripts varies greatly among individual patients, and the presence of similar levels at 3 months can therefore either mirror a substantial decline of BCR-ABL1 transcripts or only a minimal (if any) reduction of the pre-TKI value. Two more recent studies have reported similar observations in patients on first-line treatment with second-generation TKIs: a Japanese study indicated that patients with a halving time of 14 days or less had a higher likelihood to achieve major molecular response (MMR; BCR-ABL1 ≤ 0.1% IS ) and MR 4 (4-log reduction in transcript level on the IS) on dasatinib therapy [45], and a Nordic study from Finland, Sweden, and Norway suggested that a greater than 1-fold decline of BCR-ABL1 transcripts after 1 month of therapy with imatinib, nilotinib, or dasatinib is associated with better responses at 3 months and significantly higher rates of MMR [46]. To assess the early response to TKI treatment by determining the kinetics of BCR-ABL1 transcripts, a minimum of two, but preferentially more consecutive measurements would be required, e.g., at baseline and subsequently at monthly intervals during the first 3 months.…”
Section: Main Textmentioning
confidence: 99%
“…Several studies have demonstrated that the BCR-ABL1 transcript level at 3 and 6 months after starting imatinib has prognostic significance. [18][19][20][21][22][23][24]30 In a cohort of 1303 patients in the study by Hanfstein et al, 72% of patients had a BCR-ABL IS %10 after 3 months of imatinib treatment. In their study, the 5-year OS in patients with a BCR-ABL IS 10% by the third month was significantly higher than patients with a BCR-ABL IS > 10% (95.2% vs. 87%; P < .0001).…”
Section: Discussionmentioning
confidence: 99%